A new species of hill stream loach (Teleostei: Balitoridae) from Central Kalimantan, with redescriptions of Homaloptera tateregani Popta and Homaloptera stephensoni Hora - Hui, Tan Heok (Zootaxa, 2009)
Homaloptera batek, new species, is a riffle specialist differentiated by its unique colour pattern for a species of Homaloptera, consisting of a series of round blotches interspaced by smaller blotches in large individuals. The poorly known species Homaloptera tateregani and H. stephensoni are redescribed; the former is restricted to the upper Mahakam basin in East Kalimantan, whereas the latter is distributed throughout Borneo. The status of the genus Pseudohomaloptera Silas is also considered.